Improving Production Strategies through Monitoring Visual and Physicochemical Changes in Gambier Catechin-Based Shampoo Bars under Practical Storage Conditions - Rhenia Valeni; Rini; Ridwan Rizkyanto; Adila Adisti; Najla Rosyadah; Diah Ayu Natasya; Tuty Anggraini; Dina Afifah Zakia; Iin Hartati Wibisono; Daimon Syukri (Postgraduate, University of Mataram, 2026)
The development of eco-friendly cosmetics using local bioresources like Uncaria gambir Roxb. (gambir) holds strong promise for sustainable innovation. This study formulates and evaluates a catechin-based solid shampoo enriched with purified gambir extract, aiming to enhance product stability. A 14-day storage test was conducted at 20 °C and 40 °C using three types of packaging: translucent plastic, aluminum foil, and amber glass. Visual observations revealed that higher temperatures, especially in translucent plastic, accelerated color degradation due to catechin instability. Amber glass was the most effective in preserving the shampoo’s original color. Further, aqueous stability was assessed through two wet-use simulations: soaking (full immersion in distilled water) and dipping (partial immersion daily over four days). The shampoo maintained physical integrity during both tests, showing no softening or structural deformation. However, water discoloration increased over time, indicating catechin release and oxidation. The extent of browning was influenced by the pH of the water, suggesting that both environmental pH and oxidative exposure affect catechin behavior during use. These results demonstrate the solid shampoo’s physical resilience and moderate color stability under thermal and aqueous stress. While catechin oxidation is unavoidable, its rate can be mitigated through optimal packaging and pH management. The gambir-based solid shampoo shows potential as a natural, environmentally friendly personal care product, although further formulation refinement is needed to improve color retention during storage and use.